2015
DOI: 10.1002/hup.2484
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, sensorimotor, and expectancy effects on tobacco withdrawal: a preliminary study

Abstract: Objective Research designs for parsing the mechanisms underlying tobacco withdrawal are scant. This study introduced a novel research design that simultaneously manipulated three tobacco withdrawal mechanisms: pharmacological (nicotine dissipation), sensorimotor (elimination of the smoking ritual), and expectancy (activation of beliefs regarding the effects of nicotine deprivation), permitting examination of the effects of each mechanism while holding the other two mechanisms constant. Methods Following over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Future research should investigate if withdrawal‐related response expectancies influence withdrawal outcomes and/or if self‐reported withdrawal expectancies moderate reactions to stimulus expectancy manipulations (Hendricks & Leventhal, ; Juliano & Brandon, ). A future BPD study could also include a no treatment group to examine withdrawal sequelae when no vehicle is used and there is no exposure to potential drug‐related stimuli, as sensorimotor stimuli alone may impact drug and withdrawal effects (Flaten & Blumenthal, ; Guillot et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should investigate if withdrawal‐related response expectancies influence withdrawal outcomes and/or if self‐reported withdrawal expectancies moderate reactions to stimulus expectancy manipulations (Hendricks & Leventhal, ; Juliano & Brandon, ). A future BPD study could also include a no treatment group to examine withdrawal sequelae when no vehicle is used and there is no exposure to potential drug‐related stimuli, as sensorimotor stimuli alone may impact drug and withdrawal effects (Flaten & Blumenthal, ; Guillot et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A handful of prior studies have demonstrated that manipulating the expected nicotine content (i.e., dose expectancies) of nicotine replacement therapies or the types of nicotine withdrawal symptoms to expect (i.e., response expectancies) can sometimes, but not always, influence smoking choice, withdrawal, craving, and other subjective outcomes among smokers attempting abstinence (reviewed in Perkins et al, ; Guillot et al, ; Fucito & Juliano, ; Tate et al, ). There have been few experimental studies investigating expectancy effects in drug withdrawal for drugs other than nicotine (see Francis & Nelson, ; Mills, Boakes, & Colagiuri, ).…”
Section: Introductionmentioning
confidence: 99%
“…The model proposes that because nicotine acts as a pharmacological reward enhancer, 19 smoking serves to offset inherent deficient motivational responsiveness to nondrug rewards (ie, anhedonia). Then when anhedonic smokers abstain from tobacco, reward process deficits previously suppressed by nicotine become expressed and potentially exacerbated by withdrawal (which increases anhedonia levels 20,21 ). Thus, anhedonic smokers are expected to exhibit deficient responses to stimuli signaling nondrug reward, particularly when nicotine-deprived.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical interventions (e.g., behavioral activation therapy, positive mental imagery training) have demonstrated promise in reducing symptoms of anhedonia (Blackwell et al, 2015; Carl et al, 2016; Pictet et al, 2016; Williams et al, 2015) and potentially increasing smoking cessation success (MacPherson et al, 2010). There is also some evidence that pharmacologic interventions, such as bupropion and nicotine replacement, improve anhedonia during tobacco deprivation (Cook et al, 2017; Guillot et al, 2015; Paterson et al, 2007), although whether anhedonia alleviation is a mechanism of efficacy for these medications merit further inquiry.…”
Section: Discussionmentioning
confidence: 99%